Gendered Dimensions on Migration: Exploring Socio-Economic Drivers, Experiences, and Policy Implications in Nigeria - Jerry, Peace Oluchi (The Gender Truth Journal, 2025)
This paper explores the gendered dimensions of migration in Nigeria, examining how socio-economic drivers, experiences, and policy implications differ for women and men. Drawing upon feminist migration theory and neoclassical economic perspectives, the study analyzes gender-specific migration patterns, assesses the impact of existing policies, and identifies support mechanisms for migrants of different genders. By adopting a qualitative research approach, the study draws on empirical data, policy documents, and interviews to highlight the unique experiences of different genders in migration. The findings reveal significant disparities in the motivations and vulnerabilities of male and female migrants, emphasizing the need for gender-sensitive policies, with women often motivated by factors such as family reunification and escape from violence, while economic opportunities primarily drive men. The migration journey presents distinct challenges for each gender, with women facing heightened risks of exploitation and violence. Post-migration, women often encounter barriers to labour market integration and face challenges in balancing family responsibilities with economic pursuits. The study emphasizes the need for gender-responsive migration policies that address the unique needs and vulnerabilities of female migrants, promote gender equality, and ensure equitable access to opportunities for all migrants.